Teachers engaged in research : inquiry into mathematics classrooms, grades 3-5 - Langrall, Cynthia W. (Emerald Publishing Limited : IAP-Information Age Pub., 2006)
Through the chapters in this volume we learn about the questions that capture the attention of teachers, the methodologies they use to gather data, and the ways in which they make sense of what they find. Some of the research findings could be considered preliminary, others confirmatory, and some may be groundbreaking. In all cases, they provide fodder for further thinking and discussion about critical aspects of mathematics education.
"National Council of Teachers of Mathematics"--Cover.
Keywords: Mathematics -- Study and teaching (Elementary); Elementary school teaching -- Research.; Education -- Teaching -- Subjects -- Mathematics.; Primary and middle schools.; Teaching of reading, writing and numeracy.; Educational: Mathematics and numeracy.; elektronické knihy; electronic books